Hydrogeochemical characterisation and human health risk assessment of groundwater in Sultanpur District, Uttar Pradesh, India - Bhushan, Chandra; Patel, Ashish Pratap; Kumar, Arun; Pandey, Vivek Kumar; Kumar, Pavitra V.; Kumar, Pankaj; Tiwari, Ashwani Kumar (Frontiers in Water, 2025)
Groundwater resources are the primary source of different uses in the Sultanpur district of Uttar Pradesh. Hence, the present study aimed to assess the concentration of major and trace elements in the groundwater of the Sultanpur district to identify the major controlling factors of the chemical composition of groundwater and assess the quality of groundwater for drinking, domestic and irrigation uses. To achieve these goals, 58 groundwater samples were collected from the district, and the chemistry of the groundwater was analysed. The results show that the district’s groundwater was slightly alkaline in nature, with maximum EC and TDS values recorded as 1,373 μS/cm and 859 mg/L, respectively. The anionic chemistry of groundwater was dominated by bicarbonate and sulphate, while sodium and calcium dominated the cationic chemistry. The hydrogeochemical approaches and multivariate statistical analysis suggest that the rock weathering and ion-exchange processes, with limited contributions from anthropogenic activities, controlled the chemical composition of the groundwater. The concentration of TDS, total hardness (TH), fluoride, manganese, and iron exceeded the recommended drinking water acceptable limit of the Bureau of Indian Standards (BIS 2012) at several locations. The water quality index (WQI) shows that the groundwater samples were suitable for drinking purposes, except at a few sampling locations. The hazard index (HI) shows that 15 groundwater sampling locations were potentially risky to children, and seven locations have a potential risk to adults in the study area. Magnesium hazard (MH) is the most concerning parameter for irrigation usage.